Enantioselective Biosynthesis of L-Phenyllactic Acid From Phenylpyruvic Acid In Vitro by L-Lactate Dehydrogenase Coupling With Glucose Dehydrogenase - Zhang, Dong; Zhang, Ting; Lei, Yuqing; Lin, Wenqian; Chen, Xingyi; Wu, Minchen (Frontiers in Bioengineering and Biotechnology, 2022)
As a valuable versatile building block, L-Phenyllactic acid (L-PLA) has numerous applications in the fields of agriculture, pharmaceuticals, and biodegradable plastics. However, both normally chemically synthesized and naturally occurring PLA are racemic, and the production titer of L-PLA is not satisfactory. To improve L-PLA production and reduce the high cost of the NADH, an in vitro coenzyme regeneration system of NADH was achieved using the glucose dehydrogenase variant LsGDHD255C and introduced into the L-PLA production process. Here, an NADH-dependent L-lactate dehydrogenase-encoding variant gene (L-Lcldh1Q88A/I229A) was expressed in P. pastoris GS115. The specific activity of L-LcLDH1Q88A/I229A(Pp) was as high as 447.6 U/mg at the optimum temperature and pH of 40 °C and 5.0, which was 38.26-fold higher than that of wild-type L-LcLDH1(Pp). The catalytic efficiency (kcat/Km) of L-LcLDH1Q88A/I229A(Pp) was 94.3 mM-1 s-1, which was 67.4- and 25.5-fold higher than that of L-LcLDH1(Pp) and L-LcLDH1Q88A/I229A(Ec) expressed in E. coli, respectively. Optimum reactions of L-PLA production by dual enzyme catalysis was at 40 °C and pH 5.0 with 10.0 U/mL L-LcLDH1Q88A/I229A(Pp) and 4.0 U/mL LsGDHD255C. Using 0.1 mM NAD+, 400 mM (65.66 g/L) phenylpyruvic acid (PPA) was completely hydrolyzed by fed-batch process within 6 h, affording L-PLA with 90.0% yield and over 99.9% eep. This work would be a promising technical strategy for the preparation of L-PLA at industrial scale.